Enterprise Resource Planning (ERP) and Implementation Suggestion to the Defense Industry: A Literature Review - Febrianto, Tomas; Soediantono, Dwi (AGUSPATI Research Institute, 2022)
The purpose of this article is to explore the benefits of implementing Enterprise Resource Planning (ERP) in various industries and provide suggestions to be applied to the defense industry. The method of writing this article is a literature review, namely reviewing by collecting, understanding, analyzing and then concluding as many as 26 international journal articles about the implementation of Enterprise Resource Planning (ERP) published from 2014 to 2021 regarding the application of Enterprise Resource Planning (ERP) methods in various industrial sectors and defense industry. The analysis used used 25 content analysis of journal articles. The results of the literature review analysis state that the application of Enterprise Resource Planning (ERP) can have benefits for companies, namely. The results of the literature review analysis state that the application of Enterprise Resource Planning (ERP) can have benefits for companies, namely the benefits of implementing using ERP, namely to integrate financial information, to manage orders and inventories, to manage and analyze customers, to standardize and speed up production, to manage HR. , to handle procurement, to make various financial reports, taxes, sales, etc., to produce accurate complete reports that can help stakeholders make better business decisions. Based on the results of the literature review, Enterprise Resource Planning (ERP) is recommended to applied in the defense industry